2007
DOI: 10.1093/jxb/erm313
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependency of bark photosynthesis in beech (Fagus sylvatica L.) and birch (Betula pendula Roth.) trees

Abstract: Temperature dependencies of stem dark respiration (R d ) and light-driven bark photosynthesis (A max ) of two temperate tree species (Fagus sylvatica and Betula pendula) were investigated to estimate their probable influence on stem carbon balance. Stem R d was found to increase exponentially with increasing temperatures, whereas A max levelled off or decreased at the highest temperatures chosen (35-40°C). Accordingly, a linear relationship between respiratory and assimilatory metabolism was only found at mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 78 publications
2
31
0
Order By: Relevance
“…The inconsistent correlation between E s and sap flux indicated the complexity of the effect of sap flux on E s with the seasons. Wittmann and Pfanz (2007) indicated that E s measured at a given position of the stem mainly included three parts: stem respiration, CO 2 flux fixed by bark photosynthesis and CO 2 dissolved in the xylem sap. And E s in the dark was equal to actual stem respiration when bark photosynthesis and sap flux did not occur.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistent correlation between E s and sap flux indicated the complexity of the effect of sap flux on E s with the seasons. Wittmann and Pfanz (2007) indicated that E s measured at a given position of the stem mainly included three parts: stem respiration, CO 2 flux fixed by bark photosynthesis and CO 2 dissolved in the xylem sap. And E s in the dark was equal to actual stem respiration when bark photosynthesis and sap flux did not occur.…”
Section: Discussionmentioning
confidence: 99%
“…Our upscaling of E S to an annual total was based on several assumptions. First, as we used clear Perspex chambers and E S was only measured during daylight hours, we were unable to estimate bark photosynthesis (=refix-ation sensu Sprugel and Benecke 1991), which can significantly reduce apparent CO 2 efflux from young stems and twigs with a thin periderm (Cernusak and Marshall 2000;Pfanz et al 2002;Damesin 2003;Wittmann et al 2006;Breveuiller et al 2007;Wittmann and Pfanz 2007). Reification rates, however, depend mainly on woody tissue age (Benecke 1985;Pfanz et al 2002), and have been shown to decease with advancing age and hence develop a thicker periderm from 45% in 2-year-old twigs to 5% in 12-year-old branches of P. sylvestis (Linder and Troeng 1981).…”
Section: Discussionmentioning
confidence: 99%
“…67 (2010) do not play a major role in stem carbon exchange (Wittmann et al, 2006). Although of a lower magnitude than in leaves, some ecophysiological characteristics of stem photosynthesis are similar to those observed in leaves, such as the positive response of gas exchange to light and temperature (Wittmann and Pfanz, 2007;Wittmann et al, 2001), the positive response of electron transport rate to light (Manetas, 2004), and the presence of Rubisco (Berveiller and Damesin, 2008;Berveiller et al, 2007b;Schaedle and Brayman, 1986). Over a whole season, current-year stems of European beech (Fagus sylvatica) are able to assimilate the equivalent of 40% of the C lost by respiration (Damesin, 2003).…”
Section: Introductionmentioning
confidence: 89%